Cholesterol‐loaded nanoparticles ameliorate synaptic and cognitive function in Huntington's disease mice. Issue 12 (20th November 2015) - Valenza, Marta; Chen, Jane Y; Di Paolo, Eleonora; Ruozi, Barbara; Belletti, Daniela; Ferrari Bardile, Costanza; Leoni, Valerio; Caccia, Claudio; Brilli, Elisa; Di Donato, Stefano; Boido, Marina M; Vercelli, Alessandro; et al.
Abstract: Brain cholesterol biosynthesis and cholesterol levels are reduced in mouse models of Huntington's disease (HD), suggesting that locally synthesized, newly formed cholesterol is less available to neurons. This may be detrimental for neuronal function, especially given that locally synthesized cholesterol is implicated in synapse integrity and remodeling. Here, we used biodegradable and biocompatible polymeric nanoparticles (NPs) modified with glycopeptides (g7) and loaded with cholesterol (g7‐NPs‐Chol), which per se is not blood–brain barrier (BBB) permeable, to obtain high‐rate cholesterol delivery into the brain after intraperitoneal injection in HD mice. We report that g7‐NPs, in contrast to unmodified NPs, efficiently crossed the BBB and localized in glial and neuronal cells in different brain regions. We also found that repeated systemic delivery of g7‐NPs‐Chol rescued synaptic and cognitive dysfunction and partially improved global activity in HD mice. These results demonstrate that cholesterol supplementation to the HD brain reverses functional alterations associated with HD and highlight the potential of this new drug‐administration route to the diseased brain. Synopsis: Cholesterol in brain is largely derived by local synthesis. One affected pathway in Huntington's disease (HD) implicates that reduced production and/or availability of brain cholesterol may be detrimental for neuronal function. Polymeric nanoparticles (NPs) loaded with cholesterol, modified with glycopeptides g7 (g7‐NPs‐Chol) to cross the BBB after systemic injection, have been used to deliver cholesterol to the brain of HD mice. These NPs, applied for the first time to a brain disorder, are made of PLGA, which is approved by FDA in various drug delivery systems in humans. Systemic administration of g7‐NPs‐Chol (i) rescued synaptic communication in striatal medium‐sized spiny neurons, (ii) prevented cognitive decline, and (iii) restored the levels of proteins that compose the synaptic machinery in HD mice. g7‐NPs or cholesterol itself did not induce inflammatory response in the periphery, where almost all g7‐NPs are localized. Abstract : Cholesterol in brain is largely derived by local synthesis. One affected pathway in Huntington's disease (HD) implicates that reduced production and/or availability of brain cholesterol may be detrimental for neuronal function.